The SpoIIQ-SpoIIIAH complex of Clostridium difficile controls forespore engulfment and late stages of gene expression and spore morphogenesis - Serrano,M; Crawshaw,AD; Dembek,M; Monteiro,JM; Pereira,FC; Pinho,MG; Fairweather,NF; Salgado,PS; Henriques,AO (Molecular Microbiology, 2016)
Engulfment of the forespore by the mother cell is a universal feature of endosporulation. In Bacillus subtilis, the forespore protein SpoIIQ and the mother cell protein SpoIIIAH form a channel, essential for endosporulation, through which the developing spore is nurtured. The two proteins also form a backup system for engulfment. Unlike in B. subtilis, SpoIIQ of Clostridium difficile has intact LytM zinc-binding motifs. We show that spoIIQ or spoIIIAH deletion mutants of C. difficile result in anomalous engulfment, and that disruption of the SpoIIQ LytM domain via a single amino acid substitution (H120S) impairs engulfment differently. SpoIIQ and SpoIIQH120S interact with SpoIIIAH throughout engulfment. SpoIIQ, but not SpoIIQH120S, binds Zn2+, and metal absence alters the SpoIIQ-SpoIIIAH complex in vitro. Possibly, SpoIIQH120S supports normal engulfment in some cells but not a second function of the complex, required following engulfment completion. We show that cells of the spoIIQ or spoIIIAH mutants that complete engulfment are impaired in post-engulfment, forespore and mother cell-specific gene expression, suggesting a channel-like function. Both engulfment and a channel-like function may be ancestral functions of SpoIIQ-SpoIIIAH while the requirement for engulfment was alleviated through the emergence of redundant mechanisms in B. subtilis and related organisms.